Increased (Pro)renin Receptor Expression in the Hypertensive Human Brain - Mohsin, Minhazul; Souza, Lucas A. C.; Aliabadi, Simindokht; Worker, Caleb J.; Cooper, Silvana G.; Afrin, Sanzida; Murata, Yuki; Xiong, Zhenggang; Feng Earley, Yumei (Frontiers in Physiology, 2020)
Overactivation of the renin-angiotensin system (RAS)—a central physiological pathway involved in controlling blood pressure (BP)—leads to hypertension. It is now well recognized that the central nervous system (CNS) has its own local RAS, and the majority of its components are known to be expressed in the brain. In physiological and pathological states, the (pro)renin receptor (PRR), a novel component of the brain RAS, plays a key role in the formation of angiotensin II (Ang II) and also mediates Ang II-independent PRR signaling. A recent study reported that neuronal PRR activation is a novel mechanism for cardiovascular and metabolic regulation in obesity and diabetes. Expression of the PRR is increased in cardiovascular regulatory nuclei in hypertensive animal models and plays an important role in BP regulation in the CNS. To determine the clinical significance of the brain PRR in human hypertension, we investigated whether the PRR is expressed and regulated in the paraventricular nucleus of hypothalamus (PVN) and rostral ventrolateral medulla (RVLM)—two key cardiovascular regulatory nuclei—in postmortem brain samples of normotensive and hypertensive humans. Here, we report that the PRR is expressed in neurons, but not astrocytes, of the human PVN and RVLM. Notably, PRR immunoreactivity was significantly increased in both the PVN and RVLM of hypertensive subjects. In addition, PVN-PRR immunoreactivity was positively correlated with systolic BP and showed a tendency toward correlation with age but not body mass index. Collectively, our data provide clinical evidence that the PRR in the PVN and RVLM may be a key molecular player in the neural regulation of BP and cardiovascular and metabolic function in humans.